2007
DOI: 10.1074/jbc.m701523200
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activities of Human ADAMTS-5

Abstract: Aggrecanases have been characterized as proteinases that cleave the Glu 373 -Ala 374 bond of the aggrecan core protein, and they are multidomain metalloproteinases belonging to the ADAMTS (adamalysin with thrombospondin type 1 motifs) family. The first aggrecanases discovered were ADAMTS-4 (aggrecanase 1) and ADAMTS-5 (aggrecanase 2). They contain a zinc catalytic domain followed by non-catalytic ancillary domains, including a disintegrin domain, a thrombospondin domain, a cysteine-rich domain, and a spacer do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
147
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 224 publications
(153 citation statements)
references
References 52 publications
(64 reference statements)
6
147
0
Order By: Relevance
“…Our recent studies showed that the aggrecanolytic activity of ADAMTS-5 was much greater than ADAMTS-4 in both the IGD and the CS-2 regions (13). This provided biochemical evidence supporting the view that ADAMTS-5 is the major aggrecanase in cartilage catabolism and pathology.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…Our recent studies showed that the aggrecanolytic activity of ADAMTS-5 was much greater than ADAMTS-4 in both the IGD and the CS-2 regions (13). This provided biochemical evidence supporting the view that ADAMTS-5 is the major aggrecanase in cartilage catabolism and pathology.…”
supporting
confidence: 56%
“…The rabbit anti-GELE antibody that recognizes the new GELE 1480 C terminus generated by aggrecanase cleavage of the aggrecan core protein has been previously described (14). The rabbit anti-human ADAMTS-4 catalytic domain and anti-human ADAMTS-5 catalytic domain antibodies were raised in rabbits and purified as described previously (13,14). All other reagents used were of the highest analytical grade available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, however, no detectable aggrecanase-1 mRNA expression was found in chondrocytes cultured with T-2 toxin in vitro. Previous studies have shown that aggrecanase-1 usually is an up-regulated expression in the cartilage induced by IL-1 (Liacini et al, 2005;Tsuzaki et al, 2003;Pratta et al, 2003), whereas aggrecanse-2 mRNA is expressed constitutively in cartilage, and the aggrecanase activity of aggrecanase-2 was at least 1 000-fold greater than that of aggrecanase-1 (Gendron et al, 2007). Therefore, aggrecanase-2 is a major aggrecanase in cartilage metabolism and pathology.…”
Section: Discussionmentioning
confidence: 97%